Debt Relief and Leveraged Buy-Outs. (IMF Working Papers; Working Paper ;, 1988)
Analyses of debt relief that focus on the behavior of debtors and existing creditors understate the incentives for collective action by creditors. It is well known that debt relief could benefit existing creditors by providing incentives for domestic investment by residents of debtor countries. It is argued here that relief could also make available additional profit opportunities to international investors. Under these circumstances, arrangements that would allow international investors to capture economic profits would make a leveraged buy-out of existing creditors, followed by relief, a profitable strategy for any investor or group of investors that could act collectively.